Modulation of chemoresponsiveness to platinum-based agents by microRNAs in cancer - Yu, Xin (Am J Cancer Res, 2017)
Ovarian cancer accounts for the highest mortality among all gynecologic cancers. Cytoreductive surgery followed by chemotherapy with a platinum-based agent (cisplatin or carboplatin) plus paclitaxel is the first-line option for treatment of epithelial ovarian cancer. However, primary or acquired resistance to platinum-based agents is a major clinical challenge. MicroRNAs are a group of small non-coding RNAs that regulate gene expression post-transcriptionally and may function as oncogenes or tumor-suppressor genes through extensive crosstalk with intracellular signaling pathways. Importantly, their dysregulation has been implicated in ovarian tumorigenesis. Pertinent to chemotherapy, increasing evidence has revealed that miRNAs can be directly linked to chemosensitivity to platinum-based agents in ovarian cancer. In this review, we summarize current evidence concerning the role of miRNAs in prediction and modulation of cellular responses to cisplatin and carboplatin in ovarian cancer.